Análise tribológica das malhas multifuncionais obtidas por multicamadas - Aquino, Marcos Silva de (2012)
The present work consists in the analysis of tribologycal properties of basic and multifunctional knitted fabrics. This knowledge has fundamental importance for the textile industry since it can quantify, in an objective way, the tactil. The fabrics used were characterized by friction and mechanical tests for determining the viscoelastic region, wear resistance and friction coefficient of the fabrics used. The stress-strain curve was obtained by the method Kawabata, KES-FB1. Wear tests performed with the aid of equipment Martindale. The measurement of friction coefficient, two methods were used and analyzed comparatively. The first was a method already established worldwide known as KES-FB4 and the second was an innovative method called FRICTORQ, developed by the University of Minho. These two methods were compared taking into account the relative motion between the tribologycal pairs are different from each method. While the first motion is translational, the second is rotational. It was formal that the knitted had a multifunctional fabrics tribologycal performance which was better than the basic knitted fabrics, as the viscoelastic region, was laager highlighting a multifunctional structure, with greater wear resistance mainly on the back side of the knitted fabrics and lower friction coefficient. Performing a comparative analysis between two methods used to measure the friction coefficient, it was formal that both methods were consistent in terms of results. In operational terms, the FRICTORQ showed ease of operation and increased reproducibility of results